2010
DOI: 10.1159/000276996
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Weight-Dependent Toxic Effects of Chitosans on the Human Keratinocyte Cell Line HaCaT

Abstract: The cationic polysaccharide chitosan possesses bioactive properties such as antimicrobial activity, antitumor effects, hemostatic assets and positive effects on wound healing. The influence of polycations like chitosan on human cells has been reported to depend on their molecular weight. However, the mechanism of cytotoxicity caused by polycations is not yet fully understood. In the study presented, the influence of two chitosans with a similar degree of deacetylation but different molecular weight, chitosan 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 63 publications
3
34
0
Order By: Relevance
“…They actively migrated and uniformly occupied the deep layers of the chitosan scaffolds. It has been previously shown that pure chitosan with a molecular weight of 120 kDa induces apoptosis of HaCaT keratinocytes via activation of caspase-dependent signaling pathways [33]. Our results for N-TERT keratinocytes (much more "normal" than HaCaT cells) and chitosan with a molecular weight of 270 kDa contra- dict these data.…”
Section: Molecular Weight Of Chitosan and The Level Of Its Deacetylatsupporting
confidence: 77%
“…They actively migrated and uniformly occupied the deep layers of the chitosan scaffolds. It has been previously shown that pure chitosan with a molecular weight of 120 kDa induces apoptosis of HaCaT keratinocytes via activation of caspase-dependent signaling pathways [33]. Our results for N-TERT keratinocytes (much more "normal" than HaCaT cells) and chitosan with a molecular weight of 270 kDa contra- dict these data.…”
Section: Molecular Weight Of Chitosan and The Level Of Its Deacetylatsupporting
confidence: 77%
“…The results obtained indicate that LCH sponges exhibit bio-safety at lower concentration (25%) during short time (1 day). The sponges prepared in our experiment are even less toxic than chitosan 1130 which has high molecular weight [23]. However, highly concentrated extraction shows a serious toxic effect on both HSF and HaCaT cells.…”
Section: Water Absorption Behaviormentioning
confidence: 69%
“…Alternatively, chitosan might cause membrane disruption through electrostatic interaction, leading to an increase of the inflammatory cytokines IL-6 and IL-8. These cytokines have been shown to have mitogenic effects on normal fibroblasts and keratinocytes (16). Cancer cells might lose their ability to respond to the membrane-damaging effects of chitosan, such as the release of such inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%